2020
DOI: 10.1002/jbmr.4550
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ENPP1 Haploinsufficiency in Patients With Diffuse Idiopathic Skeletal Hyperostosis and Early-Onset Osteoporosis

Abstract: Homozygous ENPP1 mutations are associated with autosomal recessive hypophosphatemic rickets type 2 (ARHR2), severe ossification of the spinal ligaments, and generalized arterial calcification of infancy type 1. There are a limited number of reports on phenotypes associated with heterozygous ENPP1 mutations. Here, we report a series of three probands and their families with heterozygous and compound heterozygous ENPP1 mutations. The first case (case 1) was a 47-year-old male, diagnosed with early-onset osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 53 publications
0
28
1
Order By: Relevance
“…ENPP1 haploinsufficiency is associated with early onset osteoporosis in humans, a finding also noted in ENPP1-deficient murine models. (2,12) The loss of ENPP1 catalytic activity in ENPP1 deficiency has been proposed to induce the osteopenia in ENPP1 deficiency, but decreased PPi should result in increased and not decreased bone mass because PPi inhibits hydroxyapatite formation, which constitutes the hard mineralized matrix of bone. The low bone mass induced by ENPP1 deficiency cannot therefore be explained by an understanding of the enzyme's catalytic function alone, emphasizing that other mechanisms are likely to be involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ENPP1 haploinsufficiency is associated with early onset osteoporosis in humans, a finding also noted in ENPP1-deficient murine models. (2,12) The loss of ENPP1 catalytic activity in ENPP1 deficiency has been proposed to induce the osteopenia in ENPP1 deficiency, but decreased PPi should result in increased and not decreased bone mass because PPi inhibits hydroxyapatite formation, which constitutes the hard mineralized matrix of bone. The low bone mass induced by ENPP1 deficiency cannot therefore be explained by an understanding of the enzyme's catalytic function alone, emphasizing that other mechanisms are likely to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CKD‐MBD exhibit significant fracture risk with high subsequent mortality, and one of the primary physiologic mechanism driving these mineralization abnormalities is secondary hyperparathyroidism induced by imbalances in Ca, Pi, and vitamin D due to renal failure. Hyperparathyroidism has also been noted in patients with ENPP1 haploinsufficiency ( 12 ) and in humans and mice with homozygous ENPP1 deficiency. ( 2,14,29,33 ) ENPP1 and/or PPi deficiency may therefore exacerbate the secondary hyperparathyroidism present in CKD‐MBD, further exacerbating the aberrant bone mineralization present in renal failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recognized that enthesopathy is also frequently present in patients with other inherited FGF23-related hypophosphatemic rickets, including autosomal recessive hypophosphatemic rickets 1 and 2 caused by homozygous mutations in DMP1 and ENPP1, respectively, although other types of inherited or acquired FGF23-related hypophosphatemia are not associated with the development of enthesopathy [28,29]. Recently, we reported that haploinsufficiency of ectonucleotide pyrophosphatase/phosphodiesterase (ENPP1) with heterozygous or compound heterozygous mutations of ENPP1 is also associated with milder phenotypes of enthesopathy, manifested by OPLL and diffuse idiopathic skeletal hyperostosis (DISH) [30]. This means that the enthesopathy present in patients with XLH and ARHR1/2 is not a consequence of chronic hypophosphatemia or high levels of serum FGF23, and there is a common mechanism to develop enthesopathy among XLH and ARHR1/2.…”
Section: Enthesopathymentioning
confidence: 99%
“…As in the case with enthesopathy, conventional therapy did not improve or prevent the development of osteoarthritis in the adults with XLH, while the effect of burosumab on this complication is indecisive. [30]. This means that the enthesopathy present in patients with XLH and ARHR1/2 is not a consequence of chronic hypophosphatemia or high levels of serum FGF23, and there is a common mechanism to develop enthesopathy among XLH and ARHR1/2.…”
Section: Osteoarthritismentioning
confidence: 99%